2005
DOI: 10.1111/j.1365-2745.2005.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Species attributes and invasion success by alien plants on Mediterranean islands

Abstract: Summary1 Species attributes have been used to explain invasion patterns assuming the prevalence of biological mechanisms, although this approach often suffers several methodological and conceptual limitations, such as local idiosyncrasies, differences among habitats, phylogenetic constraints and insufficient sample size. 2 The relative importance of 15 species traits for explaining the abundance over 350 naturalized alien plant species was assessed across five Mediterranean islands (Corsica, Crete, Majorca, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
276
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(300 citation statements)
references
References 38 publications
10
276
3
2
Order By: Relevance
“…Among perennials, geophytes such as A. psilostachya and S. versicolor grow more slowly and propagate mostly by way of below-ground organs. Although vegetative propagation does not guarantee long-distance spread, it ensures rapid establishment and maintenance within suitable habitats, and successful exclusion of any possible competition (Lloret et al 2005). Numerical supremacy and the frequency of herbaceous aliens, both within the plots and along the time series, testify to their successful strategy which, on the other hand, is that of native species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among perennials, geophytes such as A. psilostachya and S. versicolor grow more slowly and propagate mostly by way of below-ground organs. Although vegetative propagation does not guarantee long-distance spread, it ensures rapid establishment and maintenance within suitable habitats, and successful exclusion of any possible competition (Lloret et al 2005). Numerical supremacy and the frequency of herbaceous aliens, both within the plots and along the time series, testify to their successful strategy which, on the other hand, is that of native species.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to explain the ecological effects of invader species have primarily focussed on their functional attributes (and how they differ from those of the resident species) and their abundance (Lloret et al 2005;Stanisci et al 2010;Vitousek 1990) or, on the habitat properties responsible for inherent vulnerability to invasion, i.e. invasibility (Chytrý et al 2008b;Davis et al 2000;Rejmánek et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, none of those studies registered any species with continuous flowering, as observed for C. procera. Long flowering periods were found to be an important attribute for invasive species in Canada (Goodwin et al 1999) and in the Mediterranean, because they increased the chances of reproductive success (Lloret et al 2005). This is an advantage over native species that exhibit seasonal flowering and strong competition for pollinators.…”
mentioning
confidence: 99%
“…In addition to the changes in the reproductive phenological pattern, C. procera showed a suite of traits that are associated with invasiveness in tropical ecosystems, such as large leaves (e.g., Lloret et al 2005), wind-dispersed seeds (e.g., Lake & Leishman 2004), hermaphrodite flowers (e.g., Reichard & Hamilton 1997), and attractiveness to humans (e.g., Cox 2004), initially as an ornamental and currently as a forage plant. The presence of all those life history attributes, combined with the observed reproductive phenological changes, might have facilitated the success of C. procera in the invasion process and reveal its potential to invade other ecosystems in the world.…”
mentioning
confidence: 99%
“…Unfortunately, islands in the mediterranean-type climates of the world tend to be located near dense human populations, and so much of the scholarship surrounding mediterranean-type islands has focused on invasion ecology (e.g. Lloret et al 2005) or the conservation of rare or endangered island endemics (e.g. Morrison et al 2011).…”
Section: Introductionmentioning
confidence: 99%